2021
DOI: 10.1177/2150132721996889
|View full text |Cite
|
Sign up to set email alerts
|

Newborns and Under-5 Mortality in Ethiopia: The Necessity to Revitalize Partnership in Post-COVID-19 Era to Meet the SDG Targets

Abstract: The Sustainable Development Goals (SDGs) were adopted during the United Nations meeting in 2015 to succeed Millennium Development Goals. Among the health targets, SDG 3.2 is to end preventable deaths of newborns and children under 5 years of age by 2030. These 2 targets aim to reduce neonatal mortality to at least as low as 12 per 1000 live births and under-5 mortality to at least as low as 25 per 1000 live births. Ethiopia is demonstrating a great reduction in child mortality since 2000. In the 2019 child mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…Individual level factors included size of a child at birth (very large, larger than average, average, smaller than average, very small); sex of child (male, female); mother’s educational level (no education, primary, secondary, higher); age of mother (15–24, 25–34, 35–44, 45 and above); father’s educational level (no education, primary, secondary, higher); mother’s occupational status (no, yes); household wealth index of (poorest, poorer, middle, richer, richest); sex of household head (male, female); current marital status (never in a union, married/living with partner, separated); breastfeeding duration (never breast fed, still breastfeeding, and ever breast fed); preceding birth interval (in months) (<24, ≥24); and birth order number (first, 2–4, >4). These explanatory variables were chosen based on previous literature, which found them to be associated with neonatal, infant, and under-five child mortality, and the report of 2019, EMDHS [ 6 , 7 , 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual level factors included size of a child at birth (very large, larger than average, average, smaller than average, very small); sex of child (male, female); mother’s educational level (no education, primary, secondary, higher); age of mother (15–24, 25–34, 35–44, 45 and above); father’s educational level (no education, primary, secondary, higher); mother’s occupational status (no, yes); household wealth index of (poorest, poorer, middle, richer, richest); sex of household head (male, female); current marital status (never in a union, married/living with partner, separated); breastfeeding duration (never breast fed, still breastfeeding, and ever breast fed); preceding birth interval (in months) (<24, ≥24); and birth order number (first, 2–4, >4). These explanatory variables were chosen based on previous literature, which found them to be associated with neonatal, infant, and under-five child mortality, and the report of 2019, EMDHS [ 6 , 7 , 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ethiopia’s situation still calls for concerted efforts by stakeholders, including scholars, to continuously generate updated empirical data to help evaluate existing healthcare systems and also to design appropriate sustainable interventions. To provide effective evidence-based interventions such as minimizing undue delays in accessing obstetric and neonatal health care services (e.g., enhancing community knowledge of neonatal death risk factors, reinforcing appropriate referral systems toward birth and complication-readiness strategy, decreasing transportation barriers, facilitating health-promoting behaviors [ 12 ]), the key role of updated scholarly evidence cannot be underestimated. Therefore, methodologically sound and nationally representative empirical studies are warranted to provide updated information to guide public policy.…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic in Ethiopia there was a shortage of supplies and infection prevention and control measures, which ultimately affected the quality of healthcare services delivery [ 15 , 27 ]. During the earlier phases of the pandemic, the routine essential healthcare services, including maternal health and child and new-born health, was challenged [ 20 , 42 , 45 ]. As a result, the healthcare system was struggling with the pandemic crises; we found that health care services such as outpatient visits, emergency room visits, inpatient admissions, declined; in addition, there were decreased numbers of elective surgical services, decreased medical, emergency and outpatient flows [ 21 ], which predisposed patients to complications.…”
Section: Resultsmentioning
confidence: 99%
“…The maternal health service utilization was found to be low, and routine vaccination coverage among children aged 15–23 months remained low and further decreased after the COVID-19 outbreak [ 22 , 26 , 43 , 46 ]. The impact of this could have long-term consequences such as failure to pursue the targets set by the Sustainable Development Goals, including a reduction of child and maternal mortality and substantial HIV/AIDS, tuberculosis, and malaria prevention and control measures [ 28 , 42 , 44 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Diarrheal diseases are the second leading cause of death among under-ve children globally (1)(2)(3)(4)(5)(6)(7), claiming more than 128, 500 death and 2.6 million illness in 2016 (8). Rotavirus is the most common cause of severe diarrheal disease.…”
Section: Introductionmentioning
confidence: 99%